Comparative evaluation of autologous platelet-rich plasma and porcine skin bandaging for wound healing in cats - Kherkar, Trupti T.; Khandekar, G.S.; Tripathi, S.D.; Gaikward, S.V.; Rohi, R.R.; Bharucha, S.V. (Indian Journal of Veterinary Surgery, 2026)
The study was conducted on 24 apparently healthy adult cats with open wounds, divided equally into two groups: group I treated with porcine skin biological bandage (n=12) and group II treated with autologous platelet-rich plasma (PRP) (n=12) on days 0, 5, and 10. Both groups demonstrated fast granulation and epithelialization. There were no significant differences in mean wound area between the groups on days 0, 5, 10 and 15; however, on day 21, group I showed significant reduction in mean wound area as compared to group II. Further, wound contraction was greater in group I, indicating more effective healing compared to group II. Physiological and haematological parameters remained stable, with no significant variations between groups at different treatment intervals. Overall, the wound healing was rated very good in group I (porcine skin biological bandages) and good in group II (autologous PRP).